Strategi Digital Marketing Melalui Sosial Media Dan Marketplace Dalam Meningkatkan Penjualan Produk - Ebenhazer Richard Handoko; Radiant Victor Imbar (Universitas Kristen Maranatha, 2026)
This internship was conducted in the Digital Marketing division of PT Jayamandiri Gemasejati (JG Motor), an official Yamaha motorcycle dealer. The internship aimed to implement and evaluate digital marketing strategies to support the company’s promotional activities. The methods applied included social media management, marketplace optimization, creative content development, and paid advertising management to increase audience awareness and engagement. All activities were integrated into daily routine tasks to comprehensively support student learning outcomes. The results indicate that the implementation of digital marketing strategies through social media and marketplaces significantly expanded product information reach (increasing awareness) and built more effective interaction and communication with potential consumers (increasing engagement). Creative content management tailored to Yamaha product categories and promotional programs played an important role in maintaining the consistency of campaign performances. Overall, this internship contributed to improving the company's brand awareness and engagement and supported the development of student competencies in the field of digital marketing.